The Relationship between Complementary Food After Exclusive Breastfeeding, Immunization and Family Income with Stunting in Kedungrejo, Malang Regency - Agie Permata, Diash; Radita Alma, Lucky; Yunus, Moch (KnE Life Sciences, 2021)
Stunting in Malang Regency has shown an increasing trend in the last three years: 22.9% in 2016, 28.3% in 2017 and 31.7% in 2018. Kedungrejo is one of Pakis Public Health Centre (PHC) working area which has an increasing prevalence of stunting. It was 38.2% in 2017, 53.1% in February 2018 and 81.8% in August 2018. This study aims to determine the factors related to stunting, which include complementary food after exclusive breastfeeding, immunization and family income. This case–control study included 30 two-to-five-year-old children diagnosed with stunting as the case group and 60 children in the same age group as the cases but not diagnosed with stunting and with no history of infectious diseases as the control group. Data were collected through interviews and documentation of the Mother and Child Book (Buku KIA) and analysed by Chi square test. The results showed that the majority of respondents were children aged 24–35 months (40%), male (62%), received complementary food after exclusive breastfeeding (54%), had complete immunization status (61%) and had low family income 63%. A bivariate analysis was used to show complementary feeding p = 0.017, OR= 2.98, immunization p = 0.032, OR= 2.88 and parents’ income p = 0.063, OR = 2.51. Keywords: stunting, complementary food after exclusive breastfeeding, immunization, family income